Germany 2 [videorecording (DVD)]. - McCormick, Megan. (Megan Leah); Shapiro, Justine (Pilot Productions, 2010)
The travelers out on a journey to look beyond the stereotypes and seek out the real Germany. Megan's journey begins in Berlin, where she visits one of the last remaining sections of the Berlin Wall, takes a tour of the city's WWII sites and explores Kreuzberg. Justine's travels begin in rural Lower Saxony, with an overnight stay at a "hay hotel" near the village of Landeloh. Also includes Planet Food--Germany.